Evaluation of lanthanide sorption and their coordination mechanism by EXAFS measurement using novel hybrid adsorbent - Awual, Md. Rabiul; Kobayashi, Tohru; Shiwaku, Hideaki; Miyazaki, Yuji; Motokawa, Ryuhei; Suzuki, Sinichi; Okamoto, Yoshihiro; Yaita, Tsuyoshi (Chemical engineering journal (Lausanne, Switzerland : 1996), 2013)
[Display omitted] •Hybrid adsorbent was prepared for selective lanthanide (Nd, Eu, Yb) sorption.•Lanthanide was strongly coordinated to hybrid adsorbent as evident by EXAFS.•Hybrid adsorbent has high sorption capacity and selectivity for potential applications.•The adsorbent exhibited high repeatability and reproducibility in several cycles. This study was investigated the trace lanthanide (Nd(III), Eu(III) and Yb(III)) sorption and recovery from wastewater streams by novel hybrid adsorbent (HA). The HA was prepared through functional immobilization of N-octyl-N-tolyl-1,10-phenanthroline-2-carboxaide into large and cage-pored mesoporous silica monolith. The adsorbent was stable and easy to adsorb and recover of lanthanide ions by complexation mechanism. The experiments were investigated to determine the effects pH, ions selectivity and lanthanide ions coordination by XAFS spectra. The lanthanide sorption were well fitted the Langmuir sorption isotherm model and indicated the maximum sorption capacities were 176.06, 163.13, and 161.81mg/g for Yb(III), Eu(III) and Nd(III), respectively. The lanthanide sorption was not affected by the presence of monovalent and divalent of sodium, potassium, calcium, magnesium, chloride, sulfate and nitrate ions due to strong tendency to form stable complexation with trivalent lanthanide. However, aluminum was strongly competed of lanthanide ions sorption due to trivalent characteristic and lanthanide sorption was greater than half of the sorption capacity without Al3+ interfering. The EXAFS data revealed that O and N donor atoms of the HA were strongly coordinated to lanthanide ions to form stable complexes. However, the bond distance of O donor atoms was shorter than N donor atoms. The adsorbed lanthanide ions were eluted with stripping agents and the adsorbent was regenerated into initial form for subsequent sorption operations after rinsing with water. The results suggested that the HA may find promising applications for selective sorption and recovery of lanthanide ions from wastewater effluents.